A concept analysis in relation to the cultural competency of the palliative care workforce in meeting the needs of young people from South Asian cultures. Issue 2 (24th April 2017) - Brown, Erica; Franklin, Anita; Coad, Jane
ABSTRACT: Objective: Our aims were to report an analysis of the concept of cultural competency and to explore how the cultural competency of the palliative care workforce impacts the holistic care of young people with palliative care needs from South Asian cultures. Method: Using keywords, we searched the online databases MEDLINE, CINAHL, ScienceDirect, and PubMed from January of 1990 through to December of 2016. Some 1543 articles were retrieved, and inclusion and exclusion criteria were applied. A total of 38 papers were included in the concept analysis. The data were analyzed using Coad's (2002) adapted framework based on Rodgers's (1989) evolutionary concept analysis, focusing on the attributes, antecedents, consequences, and related terms in relation to culturally competent care. A model case of culturally competent care was also constructed. Results: The literature provides evidence that the concept of culturally competent care is a complex one, which is often expressed ambiguously. In addition, there is a paucity of research that involves service users as experts in defining their own needs and assessing their experiences related to cultural care. Significance of Results: Cultural care should be integral to holistic patient care, irrespective of a person's race or ethnicity. There is an urgent need to involve young BAME patients with palliative care needs and their families in the development of a robust tool to assess cultural competency in clinical practice.